Selective Determination of Sudan IV in Food Using Sulfamic Acid-Modified Electrode - Chen, Meifeng; Ma, Xinying; Wang, Zhaoxia (Asian Journal of Chemistry, 2013)
A simple and sensitive electrochemical method was proposed for the determination of Sudan IV. A glassy carbon electrode was successfully modified with electropolymerized film of sulfamic acid. Cyclic voltammetry was used to study the electrochemical properties of the Sudan IV and the appropriate condition for electropolymerization process. The behaviour and method for the determination of Sudan IV were studied on the sulfamic acid modified electrode. The results showed that the sulfamic acid sensor exhibited excellent performance for detecting Sudan IV. A well-defined redox waves were obtained in phosphate buffer solution of pH = 4. The oxidation peak currents increased linearly with the concentration of Sudan IV in the range of 4.0 × 10-7 to 1.0 × 10-5 mol L-1 with a detection limit of 8 × 10-8 mol L-1. The linear regression equation is ipa (A) = 3.12 × 10-6 + 1.46c (r = 0.9974). The sulfamic acid modified electrode showed good sensitivity, selectivity and stability. The method has been successfully applied to food sample analysis with recoveries ranging from 95 to 99.5 %.